Analysis of Science Content in the Jaran Kamput Tradition of the Lombok Community - Ansumarwaty, Febiyanti; Elidayani, Evi; Hanafi, Muhammad; Andayani, Yayuk; Sedijani , Prapti (Balai Publikasi Indonesia, 2024)
Jaran Kamput is a tradition of the Lombok people that is still carried out today. The purpose of this research is to examine the science content that is relevant to the Jaran Kamput tradition. This descriptive qualitative research was conducted in Barejulat village, Jonggat sub-district, Central Lombok district. Data about the Jaran Kamput tradition were obtained through interviews and observations, then the data were analyzed descriptively to find science content relevant to the Jaran Kamput tradition. The results of this study indicate that the science content that is relevant to the Jaran Kamput tradition includes: the structure of plant tissue and its functions, natural and artificial additives, the balance of rigid bodies, and vibrations and sound waves. The results of this study are expected to be one of the alternatives for the enrichment of science materials for science teachers.